Spatial and Temporal Distribution of Precipitation Characteristics and Fitting Parameters in China - ZHOU Yu; ZHANG Yujia; MIAO Changsheng (Renmin Zhujiang)
In order to summarize the precipitation characteristics in China and explore the distribution of precipitation duration,this paper selects 56 years of continuous daily precipitation data from 698 meteorological stations in China and analyzes the spatial distribution and inter-annual variations of precipitation characteristics in terms of seasonal distribution,extreme characteristics,and precipitation duration.The paper also uses the Gamma distribution to fit the precipitation duration curves and estimate the parameters and analyzes the potential factors that affect the fitting parameters.The results show that ① the precipitation generally shows an increase in the southeast part and a decrease in the central part of China,with an increase and a wider distribution of winter precipitation in the east,northwest,and northeast parts.From the southeast to the northwest of China, the trend of precipitation percentile change shows an increase,then a decrease,and then an increase again,and the distribution of the 99-percentile precipitation thresholds is more uneven.The trend of the precipitation percentile at the Linhe station shows the greatest decrease,especially the wet-day precipitation percentile.The wet period is in a decreasing trend in the southwest and central parts and in an increasing trend in the coastal and northwestern parts.The distribution characteristics of drought and flooding durations in the basin show the opposite state in most regions,and the inter-annual variation of the wet period is smaller than that of the dry period.② The Gamma distribution has a better fitting effect on precipitation.The scale parameter β has a higher correlation with precipitation amount and precipitation percentile and better performance on extreme precipitation thresholds for heavy precipitation events.These findings can provide theoretical support for the subsequent research on precipitation processes based on physical influencing factors.